Can mindfulness help my career?”: A talent development perspective (A) - REB, Jochen (Institutional Knowledge at Singapore Management University, 2024)
The two-part case study discusses the challenges faced by the two talented professionals in their respective careers and the influence of mindfulness on their growth and development. Case A focuses on mindfulness concepts applied to help unlock talent while Case B builds on the former case of mindful career development but introduces the additional role of mindful supervision in talent management. This case also focuses on how mindfulness can support the organisation in building a talent pipeline and succeed in the ‘war for talent’. In Case A, Astrid was newly promoted to the Head of Marketing in her company’s head office in Spain. Moving over from Denmark, she continued to perform well in the new strategic role and was selected to the talent pool for future senior leaders. However, her straight-talking style ruffled the feathers of local co-workers. Case A explores basic questions that are relevant to career managers like: how can one use mindfulness to better unlock their talents and progress in their careers? In Case B, Munn was a young commercial analyst in Singapore who aspired to become a business leader. His track record of good work performance landed him in the talent pool for young future leaders and he was offered the option of choosing between a safe or a risky career track. Fortunately for Munn, his talent pool mentor was an experienced leader who was open to discussing his concerns and providing mindful support. Case B explores not only how mindfulness can unlock the talent of a person, but also provides insights into questions relevant to experienced leaders like: “How can leaders’ mindfulness unlock the talent of their subordinates?” and “How can mindfulness help leaders build a strong talent pipeline for the organisation?” Students will learn the concepts of talent management and mindfulness in the workplace and may experience mindfulness through an optional practice. They will discuss how mindfulness can help a talented employee in career progression. In addition, a supervisor’s mindfulness also plays a key role in unlocking the full potential of their subordinates. Finally, students will learn how mindfulness can advance talent development and guide an organisation towards effective competition for top talent.